Strategies Musicales de Preservation et D’Adaptation chez les Ukrainiens-Montrealais - Berthiaume-Zavada, Claudette (MUSICultures, 1989)
Claudette Berthiaume-Zavcida tells how Ukrainian-Canadians in Montreal have preserved and adapted their folk music. Although their numbers are small, they have maintained elements of their native dances and songs while adapting to modern conventions. In their new compositions they use traditional forms, melodies, rhythms, and common speech.